Self-Regulated Learning dan Self-Control Pada Mahasiswa Pendatang - Rinawati Rinawati; Liza Adyani (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2020)
Educational isn't always between teacher and student, even each individual can arrange their learning or what is called learning with their arrangements. This of course requires good self-control from every learner. This study aims to determine the relationship between independent learning and self-control in students through a cross-sectional approach. The population and sample of this study were West Sumatra 2016-2018 students studying at Malikussaleh University using quota sampling. Primary data collection is done by utilizing self-regulated learning scales and self-control scales. Hypothesis test results indicate the value of the correlation coefficient (r = 0.553) at a significance level of 0,000 (p <0.001). The state of this statistical value can be interpreted that the working hypothesis has a significant relationship between the two variables studied.